ADAPTIVE-COMPREHENSIVE POLICY: LEVERS OF LONG-TERM HUMAN DEVELOPMENT IN LOCAL GOVERNMENT - Mutia Rahmah; Riska Amelia; Muchlis Hamdi; Amy Yayuk Sri Rahayu (Natapraja, 2025)
The trend of increasing HDI in Indonesia for the last few decades does not exceed 2% annually. In fact, human development is a critical factor in increasing the nation’s quality of life. Although a bunch of studies have been done dealing with its determining factors, there is no available generalized conclusion on such determinants. This article aims to find out the empirical factors determining human development in Indonesia. The regression data panel analyzed data from 34 provinces between 2010 and 2024, sourced from the Ministry of Finance and Statistics Indonesia, utilizing STATA 17.0. The results showed that there were seven factors that influenced the success of human development in Indonesia by 85.31%. This finding also indicates that each factor has different strengths and directions of influence simultaneously or partially, implying the need to increase HDI with selective action in the form of determining policy priorities. Such policies can be a lever for the success of long-term human development, and in turn, become the foundation for the development of adaptive and comprehensive policies in local governments. The future study that needs to be carried out on the Gini ratio, which represents inequality, should have implications for HDI and local spending anomalies as a continuation of the findings of this study.